MODELLING OF DYNAMIC PICTURE OF BUDGET AND INTER-BUDGET RELATIONS REALIZATION BASED ON NON-LINE WAVE MECHANISM OF ECONOMIC ENTITIES INTERACTION - T. V. Ogorodnikova; P. A. Ogorodnikov (Научный вестник МГТУ ГА, 2016)
The article considers opportunities of using mathematical instrument of non-line waves theory for the purposes of steady budget process modelling; introduces a concept of budget field; is introduced, its characteristics (energy, impulse); are formalized their proportionality is determined.